2006
DOI: 10.2337/diabetes.55.02.06.db04-0195
|View full text |Cite
|
Sign up to set email alerts
|

Integrin Signaling via RGD Peptides and Anti-β1 Antibodies Confers Resistance to Apoptosis in Islets of Langerhans

Abstract: Islet transplantation is associated with a high rate of early graft failure caused by early immune attack and poor functionality of islets. Apoptosis of islet cells appears soon after islet isolation and primarily involves the ␤-cell. The purpose of this study was to determine the effect of ligation to extracellular matrix (ECM) proteins on survival of the islets of Langerhans following islet isolation. Islets that had been cultured for 24 h on collagen type I showed an islet survival of 59.7 ؎ 8.7%, while isl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
128
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(132 citation statements)
references
References 40 publications
2
128
0
1
Order By: Relevance
“…Among these, laminins were found to induce Insulin gene expression and increase b-cell proliferation in islets from VEGF-A tissue-specific knockout mice that do not have normal amounts of laminin surrounding the b-cells [26]. Laminins also enhance survival and function (glucosestimulated insulin secretion) of isolated islets [28][29][30]. Laminins are complex proteins composed of three subunits (a, b and g) with sizes ranging from 400 to 800 kDa (depending on subunit composition) [31,32].…”
Section: Onward Ngn3mentioning
confidence: 99%
“…Among these, laminins were found to induce Insulin gene expression and increase b-cell proliferation in islets from VEGF-A tissue-specific knockout mice that do not have normal amounts of laminin surrounding the b-cells [26]. Laminins also enhance survival and function (glucosestimulated insulin secretion) of isolated islets [28][29][30]. Laminins are complex proteins composed of three subunits (a, b and g) with sizes ranging from 400 to 800 kDa (depending on subunit composition) [31,32].…”
Section: Onward Ngn3mentioning
confidence: 99%
“…For instance, glucose-stimulated insulin secretion is greater when islets are cultured on surfaces treated with ECM molecules such as collagen type I or IV, laminin, fibronectin, or arginineglycine-aspartate (RGD) peptides. 53,[114][115][116] These findings indicate that incorporation of these ECM factors on the surface of the encapsulation material may improve islet survival and function. The exploitation of integrin/ECM interactions may also prove to be a vital element in creating a viable bioartificial pancreas.…”
Section: Additional Strategies To Increase Islet Cell Survival and Fumentioning
confidence: 82%
“…86,112,113 Additionally, islets cultured on surfaces treated with anti-b 1 or anti-a 1 antibodies show an increase in cell survival and glucose-stimulated insulin secretion. 53,[114][115][116] In addition to the use of integrin antibodies, ECM mimicry can be accomplished through incorporation of other ECM proteins and peptides.…”
Section: Additional Strategies To Increase Islet Cell Survival and Fumentioning
confidence: 99%
“…Some synthetic peptide epitopes have been identified that mimic the effect of ECM proteins by binding to the integrins. Arginine-glycine-aspartic acid is the most extensively studied epitope which reduces the apoptosis rate of islets (101). Transplantation of islets in a fibroblast populated collagen matrix is also used to prevent anoikis in which fibroblasts produce fibronectin and growth factors to enhance viability and functionality of the islets (102).…”
Section: Prevention Of Anoikismentioning
confidence: 99%